The Effect of Company Growth and Leverage on Financial Performance in Manufacturing Companies in The Pulp and Paper Sub-Sector Listed On The Indonesia Stock Exchange for the Period 2021-2023 - Elisabeth Dewi Anggraini; Susanto, R. Y.; Nurhidayat, Moch (International Journal of Management and Business, 2025)
A company's performance can be assessed through its financial performance. Financial performance is one of the important indicators to assess the success of a company. This research aims to determine the effect of Company Growth and Leverage on the Financial Performance of the Pulp and Paper Subsector Companies listed on the Stock Exchange, both partially and simultaneously. The research sample was obtained using purposive sampling techniques, resulting in 9 sample companies for the research period 2021-2023. The data techniques used include documentation, with data analysis techniques employing classical assumption tests and multiple linear regression, while hypothesis testing utilized t-tests and f-tests. The results show that company growth has a positive and significant effect on financial performance, while leverage has a negative and significant effect. Simultaneously, both affect financial performance, so the balance between business expansion and debt management is very important. Manufacturing companies in the pulp and paper subsector need to manage growth optimally and maintain a healthy capital structure to maintain stable and sustainable financial performance